Όταν οι Μοσχοπολίτες ταξιδεύουν στην κοιλάδα του ποταμού Σίνβα. Οι εγκαταστάσεις των Μοσχοπολιτών στο Μίσκολτς μέσα από το κρατικό αρχείο της ουγγρικής πόλης - Καρακώστα Κωνσταντίνα (Μακεδονικά, 2011)
Moschopolis was a mountain vlach settlement which rapidly grew to oneof the most important trade and small industry centres of the South Balkanpeninsula by being a part of the Ottoman Empire preferential status. Thecommercial contacts of its inhabitants initially with Venice and, after the signature of the Karlovic and Passarovic Treaties, with many of the developingcentres of the Balkans and Central Europe, marked the turn of theMoschopolis people from a limited stock farming activity to their entering thewider European family of commerce.The study of the Greek communities’ historical presence in the territories oftoday’s Hungary leads directly to the Byzantine Empire era. The ottoman conquest which followed caused the vivid immigration of many Greeks mainly fromWestern Macedonia who arrived in the christian country looking for a refugefrom the muslim conqueror. Their settlement in Miskolc is estimated around theend of the 17th century. Their presence in the city’s bazaars during this timeproves the clearly professional character of their common activities (company).This character will develop to be the basis of a civic community form.From the first quarter of the 18th century onwards the merchants who settled temporarily or permanently to Miskolc came from Moschopolis. Miskolc hadalready been declared an imperial estate thus gaining even more opportunitiesfor rising to wealth. The lists of the census of the area, which were written inLatin, the official language of the Hapsburg administration, clearly depictMoschopolis to be the main place of origin of the merchants who arrived inMiskolc from Turkish grounds. The vlach descent of the people of this former vibrant city of Macedonia is also recorded in the lists of the municipal authorities.In the end, the use of the terms «vlach» and «macedóvlach» marked thecommercial community of Miskolc which, according to the census lists, continued to grow significantly until a few years before the end of the 18th century. The number of the community members has been observed to considerablydecrease during the last decade of the 18th century and even more so after thebeginning of the 19th century. From a more general point of view we see thatGreek merchants settled and finally dominated in Miskolc gradually and alwaysin parallel with those elements which guaranteed their economic stability